Empreendedorismo materno como escolha profissional : histórias de vida - Costa, Deise Araujo Chagas (2022)
Faced the needing of establish socially themselves, confronting the salary disparities between genders and better manage the triple working schedule, which requires being great mothers and housewives, besides their professional performance, many women started to undertake. This study focuses on women who undertake and are also dedicated to motherhood, a phenomenon called mumpreneurs (Maternal Entrepreneurship). Entrepreneurial mothers are breaking new ground in their business practices, redefining their entrepreneurial identities in search of congruence between their roles as good mothers and businesswomen, making studies about this phenomenon. Faced with this challenge, Breen and Leung (2020) proposed a conceptual model that offers an initial perspective for understanding the entrepreneurial career, locating entrepreneurial mothers within their relational contexts. The relational lens offers an explanation of how relational contexts influence the choice for entrepreneurship, shape perceptions of opportunities, influence choices, the shape and process of business expansion over time. However, this model needs to be better appreciated, given this possibility, and this study aims to analyze, based on the conceptual model of Breen and Leung (2020), how the relational context, choices and relational results collaborate to women in Aracaju to choose to undertake after motherhood. As for the methodological procedures, the approach was qualitative and exploratory. The research was conducted with the help of the oral life history biographical method. Data were collected using in-depth interviews and analyzed using the content analysis technique. After investigating the findings, it was possible to verify in practice the existence of the relationships proposed by the conceptual model of Breen and Leung (2020). In particular, the relational context highlighted how much motherhood and family members can influence women's decision to undertake post-maternity, a choice that was aligned with the personal values of these mumpreneurs. Regarding to relational choices, the entrepreneurial mothers obtained the necessary family aid to support the professional decision. The results achieved with the professional change deconstructed the idea of success related only to financial gains, so that these results were extended to the children and family members of the interviewees.